Atividade antifúngica in vitro e in vivo de extratos de Sapindus saponaria frente a isolados vaginais sensíveis e resistentes aos azólicos - Damke, Edilson (2009)
Vulvovaginal candidiasis (VVC) is an infection that affects several women worldwide every year, determining a great discomfort, interfering upon emotion and sexual relationships and resulting labor development damage. For VVC treatment azoles has been usually used, beside of polyenic agents (nystatin and amphotecin B). However, it has been noticed a low therapeutic expectative with nystatin, whereas the azoles present high cost; which makes difficult the patient's management with infection, pointing out the need of new alternatives. Recently, Sapindus saponaria demonstrated excelent in vitro fungicide activity against C. albicans and non-albicans, which was superior to fluconazole that is only fungistatic and already reveals a resistance profile. It has been carried out a study of chemical, toxicity, in vitro and in vivo antifungal activity of hidroalcoholic extract (HAE) and butanolic extract (BUTE) of Sapindus saponaria against vaginal Candida spp. susceptible and resistant to azoles. The extracts were made with dry pericarps and its in vitro antifungal activity, as well as fluconazole (FLU) and intraconazole (ITRA) were determined by broth microdilution, defining values of minimum inhibitory concentration (MIC) and minimum fungicide concentration (MFC) of 46 isolates of C. albicans and 10 of C. glabrata from patients with proven VVC. The infection was induced in hyperestrogenic female Wistar rats with susceptible C. albicans (SCA), resistant (RCA) and resistant C. glabrata (RCG) to azoles. The animals were intravaginally treated with HAE and BUTE at 1%, 2.5% and 5%, and FLU at 100 µg/mL, at the periods of 1, 24 e 48 h after infection, followed by culture and scanning electron microscopy (SEM). The data resulted on the article writing "antifungal activity in vitro and in vivo of Sapindus saponaria against Candida sp vaginals susceptible and resistant to azoles". The extracts demonstrated effective in vitro inhibitory and fungicide activity to all isolates, with MIC and MFC values a bit higher than the ones for C. glabrata. The infection was eliminated with CAE and BUTE without citotoxic action. Our results reveal that AE and BUTE of S. saponaria are very promising sources for the development of VVC antifungal drug.